Analisa Perancangan Sistem Pengelolaan Data UMKM berdasarkan Business Intelligence Development Model Framework - Ardhin Primadewi; Tuessi Ari Purnomo; Dimas Sasongko (STMIK Budi Darma, 2021)
Increasing data and information needs for Micro, Small and Medium Enterprises (MSMEs) is the basis for MSME actors to expand. The data and information needed are in the form of strategic data from the collective results of similar SMEs in a certain scope to determine market conditions objectively. This research analyzes in-depth using the BIDM Framework which helps planning long-term system development that is not limited only as a data repository and report reporting, but also to predictive analytics, data mining, trend analysis, data visualization, dynamic reports and others. The BIDM framework focuses more on the BI-based system development plan instead of BI implementation by taking into account 6 characteristics. The results of the BIDM Framework Analysis are adjusted to the conditions of MSMEs in Magelang disstrict is then prioritized using value chain analysis. The final result is a system menu design recommendation and database design that pays attention to entities and attributes that match the needs of business intelligence analysis.